Preliminary evaluation of associated viruses in production systems of cape gooseberry, purple passion fruit, and rose - Cutler, Joseph; Langer, Juliane; Susanne, Von Bargen; Acosta Losada, Orlando; Casierra Posada, Fanor; Castañeda Cárdenas, Adriana; Betancourt Vásquez, Mónica; Cuellar, Wilmer; Arvydas Stasiukynas, Eduardo; Altenbach, Denise; Büttner, Carmen (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 390-396).